Satellite Image enhancement using Combination of Transform Techniques and Interpolation Methods (International Journal of Engineering and Computer Science, 2014)
Satellite images are used in many fields of research and enhancement of these images is an important process. In this paper we discuss the different types of transform techniques used for image enhancement. The edges of an image can be improved by using an effective transform technique and the resolution can be improved by using interpolation technique. The combination of transform techniques and interpolation methods helps to produce an overall enhanced image. The different transform techniques discussed in this paper are DWT, CWT, SWT and Curvelet Transform